Quality of life of fitness professionals in Portugal: Comparative and correlation study - Vieira, Isabel; Esteves, Dulce; Ramos, Liliana; Simões, Vera; Franco, Susana (Frontiers in Psychology, 2022)
Fitness has been revealing a positive impact on the quality of life (QoL) of practitioners and fitness professionals (FPs) represent a role model for their customers in the fitness industry, emphasizing the need to know their QoL indices. The purpose of this study is to characterize the QoL of FPs in Portugal, compare it between groups and correlate QoL with sociodemographic and work-related variables. A total of 388 FPs answered an online survey about sociodemographic and work-related variables and the Portuguese version of the World Health Organization Bref QoL Assessment. Descriptive analysis, t-test, ANOVA, Kruskal-Wallis, Pearson and Spearman were used for statistical analysis. The results suggest that FPs in Portugal have different levels of QoL, considering the high standard deviation, with lower average indices than other countries. The lowest scores of QoL were verified in the environment domain. The results of the comparison between groups suggest that being male, married and having a master’s degree or higher were the characteristics with better indices of QoL. Age, professional experience and net salary reveal a positive relation/association with QoL. Body&mind group classes (GC) per week, maximal GC per day, paid and unpaid working hours per week and annual expenses related to the profession reveal a negative relation/association. Maximal GC per day results could be an important finding to help minimize the physical problems among FPs and body&mind GC per week results could be an indicator of the FPs adaptation that allows them to remain on the profession. Unpaid working hours per week has the highest number of significant relations/associations with QoL. These findings could be important to improve the QoL of FPs. Thus, they could result in better work capacity and, therefore, fewer professionals would abandon the profession. It would also have a positive impact on the fitness industry and on the promotion of physical activity for a healthier society. More research is needed regarding the QoL of FPs.